Research Methodology : A Step-by-Step Guide for Beginners - Kumar, Ranjit (Nodia Pearson Education, 2005)
For introductory research courses across multiple disciplines in the social sciences. This second edition of "Research Methodology: A Step by Step Guide for Beginners" is designed specifically for students who do not have any previous experience or knowledge of research and research methodology. This practical step-by-step approach provides students with a strong framework of methods and procedures used in both quantitative and qualitative research covering the different concepts through the use of simple examples and providing theoretical knowledge in a simple to complex progression. This clear and concise text focuses on developing research skills in students through providing qualitative and quantitative approaches in an integrated manner
Include References and Index
Keywords: Social Sciences Research Methodology -- Social Science methods -- Methodologie